Wood-based flexible graphene thermistor with an ultra-high sensitivity enabled by ultraviolet femtosecond laser pulses. Issue 1 (2021) - Kim, Young-Jin; Le, Truong-Son Dinh; Nam, Han Ku; Yang, Dongwook; Kim, Byunggi
Abstract: Real-time monitoring of temperatures over extensive free-form surfaces of precision machines, smart products, and human bodies with a high resolution can provide invaluable information for smart manufacturing, Internet-of-Things, and advanced healthcare. However, traditional rigid thermistors could not be conformally attached on arbitrarily curved surfaces. In this study, a high-resolution flexible graphene thermistor is demonstrated by transforming wood into laser-induced-graphene via ultrafast laser pulses and subsequent transfer to flexible substrates. This thermistor provides a 16-times higher resolution than the state-of-the-art counterparts which was applied to precise temperature monitoring of an electric motor, glass cup, and human hand.